Analisis Risiko Keselamatan dan Kesehatan Kerja Di Rumah Makan Saung Baraya - Kenny; Tasia Paulina; Handi Wilujeng Nugroho (Scientific Literacy Innovation and Technology Journal, 2024)
Even though Indonesia has laws related to K3, cases of work accidents are still high, including in the food services sector. Accidents in restaurants can be caused by various factors such as work procedures that do not comply with standards, human error, and lack of protective equipment. This research aims to assess K3 risks in the Saung Baraya restaurant, identify occupational risks, and provide prevention efforts. The research results show that the Saung Baraya restaurant has a high risk of accidents, including fires, electrical accidents, falls and injuries caused by sharp tools. Risk evaluation is carried out by direct observation and the use of risk assessment standards. Risk control is carried out by paying attention to fire prevention, use of personal protective equipment, infrastructure improvements and changes to work procedures. The implementation of K3 in the Saung Baraya restaurant still needs to be improved. Insufficient understanding of K3 and lack of use of personal protective equipment causes major accidents. To reduce risks, efforts are needed such as using PPE, improving infrastructure, and increasing worker awareness of potential dangers. This will provide benefits not only to workers, but also to business owners and consumers.